Synthesis of rod-shaped Au-Cu intermetallic nanoparticles and SERS detection - Singh M.K.; Chettri P.; Basu J.; Tripathi A.; Mukherjee B.; Tiwari A.; Mandal R.K. (My University, 2025)
Intermetallic phases in Au-Cu nanoparticles has been synthesized chemically in liquid phase. The heat-treatment of these nanoparticles at 180 °C for 1 h in solution phase led to the formation of Au-Cu alloy nanoparticles with nearly spherical shapes and monodispersed size of ∼10 nm. Subsequent heat-treatment at 300 °C for 30 min of these Au-Cu alloy nanoparticles not only revealed structural transformation to intermetallic phases (tetragonal AuCu (tP4) and cubic Cu 3 Au (cP4)) but also shape change occurs from spherical to rods having average aspect ratio ∼3.0. The structural determination at the particle has been carried out through nano-beam electron diffraction coupled with simulation of electron diffraction patterns and high resolution phase contrast images. These Au–Cu intermetallic nanoparticles exhibit an excellent surface enhanced Raman spectroscopic activity with methylene blue compared to that of Au-Cu alloy nanoparticles. © 2019 Elsevier B.V.